Potential Yield of Glutinous Rice Varieties (Oryza sativa L. Var. glutinosa) Under Different Water Supply - Yuli Yarwati (JURNAL PANGAN, 2023)
Rice is a Gramineae plant. Each rice plant type has different morphology, physiological characteristics, and yields. Thus, genetic and environmental factors such as water availability influence those differences. West Nusa Tenggara (NTB) is one of Indonesia’s provinces with local glutinous rice strains cultivated by farmers. Local glutinous rice is grown on a field scale which depends on rainfall in this region. Therefore, plant growth rate and yield might decrease caused by inadequate amount of water during plant growth and development. Hence it is essential to find out the response of several strains of glutinous rice due to different water supplies, in addition to obtain adaptive glutinous rice strains under water deficit. This research was a factorial experiment with a randomized group design that contained two factors. The first factor was glutinous rice varieties, consisting of three local glutinous rice types: Me’e, Kala, Samada, and one National variety, Paketih. The second factor was the field capacity condition implemented by the amount of water supply: 2,250 ml (50 percent FC), 3,375 ml (75 percent FC), 4,500 ml (100 percent FC), and 5,625 ml (125 percent FC). Data were analyzed using a 5 percent analysis of variance, then proceeded with DMRT. The results showed that glutinous rice strains and water supply interacted with weight grains per clump. Meanwhile, there was no interaction on plant length, number of leaves, and weight of 100 grains. Samada variety showed adaptive behavior under limited water, presented on yield variable compared to the other varieties.